Chilocoris capensis n. sp., the first species of the genus Chilocoris Mayr, 1865 (Hemiptera: Heteroptera: Cydnidae) recorded in the Republic of South Africa with an annotated checklist of South African burrower bugs - Lis, Jerzy A.; Lis, Barbara; Compton, Stephen G. (Zootaxa, 2016)
Chilocoris capensis n. sp. collected from fallen ripe figs of broom cluster fig Ficus sur Forsskål, 1775, the first burrower bug species of the genus Chilocoris Mayr, 1865 recorded in the Republic of South Africa, is described and compared with Chilocoris laevicollis Horváth, 1919, the morphologically most closely allied Afrotropical species. Additionally, an annotated checklist of burrower bug species recorded in the Republic of South Africa is provided. The known biology of Afrotropical Chilocoris species is briefly summarized.